Semantic interoperability of GIS and MCDA tools for environmental assessment and decision making. (February 2018) - Jelokhani-Niaraki, Mohammadreza; Sadeghi-Niaraki, Abolghasem; Choi, Soo-Mi
Abstract: A promising approach to environmental assessment and decision making analyses is based on integrating Multicriteria Decision Analysis (MCDA) and GIS tools. Integration of GIS and MCDA tools can be potentially achieved through interoperability, where these tools can exchange relevant information to tackle a particular environmental problem. However, the problem of semantic heterogeneity caused by different meanings of data, terminologies, and models used in GIS and MCDA has been recognized as an obstacle in the interoperability of these tools. Conventionally, exchange of data between GIS and MCDA systems for environmental applications relies on prior knowledge to mediate meanings between the two components. This paper proposes an ontology-enabled framework for semantic interoperability of GIS and MCDA web services. In particular, this study has made significant contribution to environmental decision making by providing an interoperable framework to exchange environmental data with intended and unambiguous meanings between GIS and MCDA services. Highlights: This paper proposes an ontology-enabled framework for semantic interoperability of GIS and MCDA components. It shifts the paradigm of environmental decision support systems from application-specific to a semantic interoperable framework. The approach uses a set of ontologies to address the challenges of semantic interoperability between GIS and MCDA tools.